Corporate Governance for Mitigating Financial Distress during COVID-19 in Non-Financial Firms on Indonesia Stock Exchange - Rohman, Naufal Aulia; Suhardianto, Novrys (Accounting Analysis Journal, 2024)
Purpose: This study aims to examine the effect of corporate governance mechanisms on financial distress using the proxies of institutional ownership and independent commissioners during the COVID-19 pandemic from 2020 to 2022. Method: The research involves a robust sample of 886 companies listed on the Indonesia Stock Exchange, excluding the financial industry. Through the application of logistic regression analysis using SPSS 29, a thorough examination of the data is conducted to unravel the intricate relationship between corporate governance mechanisms and the probability of financial distress. Findings: The results showed that the corporate governance mechanism proxied by institutional ownership and independent commissioners was proven to reduce the probability of financial distress during the COVID-19 pandemic from 2020 to 2022. Novelty: As a result, this study successfully presents empirical evidence that supports the need for companies to implement good corporate governance to prevent potential business risks such as financial distress both under normal conditions and during unpredictable crises such as the COVID-19 pandemic.